Treatment of copper-containing leaching residue by sulfation roasting followed by acid/water leaching - Shirchinnamjil, Nyamdelger; Tumen-Ulzii, Narangarav; Davaadorj, Nemekhbayar; Byambasuren, Khulan; Purevsuren, Sarantsetseg; Erdenebat, Ulziibadrakh; Surenjav, Enkhtuul (Mongolian Journal of Chemistry, 2023)
This research investigates the extraction of copper from copper-containing leaching residue, which includes 33.45% of copper, 14.14% of iron, 23.87% of sulfur and trace amounts of silver and other elements. Roasting the copper-containing residue under air and oxygen flow convert sulfides into sulfate, followed by water and acid leaching to extract copper. The process parameters, including leaching temperature, sulfuric acid concentration, leaching time, solid-to liquid ratio, and agitation speed, were optimized for both water and acid leaching methods. Results showed that the maximum copper dissolution efficiency was 93.12% with water leaching, and 97.16% with acid leaching. Chemical analysis revealed that the water and acid leaching residue contained 48.13% and 31.64% of iron, respectively. This study provides valuable insights into the process optimization for copper extraction from copper-containing leaching residue, which can inform the development of more efficient and sustainable methods for metal recovery.